Formação continuada de professores do Ensino Fundamental II: necessária, complexa e urgente - Alfonsi, Selma Oliveira (2018)
This research aimed to investigate whether the demands placed on the secondary school teachers are taken into account by the continuing educational processes they have, compared to what they live at school. The option for carrying out this research, focused on the secondary school, is due to the fact that important issues are raise in this context that require assertive teachers mediations, as those issues may have an impact on children and adolescents learning process. We believe that the continuing education in service is an important tool to introduce teachers in their working environment and potencialize their practices. Being able to teach in a secure way and being aware of their choices can help teachers to improve their students learning skills and build their project of life. This is a qualitative research carried out with six school managers (one principal and five coordinators) and 41 teachers from two public schools in the city of São Paulo, that take part in Programa de Ensino Integral -PEI, (that is an educational program which students spend the whole day at school). For data gathering it was applied a questionaire to the teachers and interviews were conducted with the managers. The theoretical approach used was the one related to teaching education field, such as, Canário (1998, 2001), Fullan e Hargreaves (2000), Nóvoa (1992), Marcelo Garcia (1999), Gatti e Nunes (2009), Gatti (2003, 2010), Imbernón (2011, 2009), Libâneo (2015, 2012, 2007), Marcelo (1999), Marcelo e Vaillant (2012), Davis et al. (2012a, 2012b), Shulman (1987). The data analysis was done by using some of the principles of content analysis by Bardin (2011). Data were gathered in two categories: Educational actions: places and the participation of teachers and managers; The teachers education in school: guideliness, themes and teachers opinion about them; 3. The continuing education on the secondary school: challenges and needs. The first hipothesis of this thesis was that the educational processes experienced by the teachers might not help them to face the existing challenges at school. The result showed that, at the schools where this research was held, as they have a systematic teachers educational program, closely wached by the managers, their needs are somehow fulfilled. It was also possible to notice that PEI is a program which brings oportunities to teachers and students to develop their potencialities. It’s worth pointing out the role of the area coordinators in the development of the teachers education in those schools